Altered production of membrane-associated proteins, providing iodine accumulation by thyroid gland, after exposure to endocrine disruptor DDT - Obernikhin, Sergey S.; Yaglova, Nataliya V.; Nazimova, Svetlana V.; Yaglov, Valentin V. (Experimental Biology and Biotechnology, 2020)
Exposure to endocrine disruptors has a sufficient impact in rise of thyroid disorders. Iodine accumulation by the thyroid is provided by sodium iodide symporter, a glycoprotein, located in the basolateral membrane of thyroid cells. Therefore, sodium iodide symporter might be a putative target for endocrine disruptors. Objective of the research – investigation of sodium iodide symporter production after long-term exposure to endocrine disruptor dichlorodiphenyltrichloroethane (DDT) in different periods on postnatal development. Newly borne and 7-week old male Wistar rats were exposed to low doses of DDT during 6 and 10 weeks. Expression of sodium iodide symporter in thyroid cells was evaluated by immunohistochemistry. Quantification of sodium iodide symporter, thyroid hormones (T3 and T4) and thyroid stimulating hormone (TSH) in serum was performed by enzyme-linked immunosorbent assay. The investigation also included morphological examination of thyroid slides and morphometry. Adult rats after 6 weeks of exposure showed diminished level of total T4 and increase in T3 production, associated with significantly lowered TSH and sodium iodide symporter serum concentration. Rats, exposed to endocrine disruptor since birth, demonstrated slight decrease in T4 and sodium iodide symporter. Reduced level of free T3 and elevated serum TSH were found in adult rats after 10 weeks of exposure. Exceeded level of serum sodium iodide symporter was revealed. It was provided by increased number of thyroid cells, producing this protein, due to formation of numerous microfollicles in the thyroid gland. Young rats after 10 weeks of exposure demonstrated diminished total and free T3 levels and elevated TSH. No up-regulation of sodium iodide symporter expression was found. Morphological examination revealed enlarged follicles and no microfollicular rearrangement of thyroid parenchyma. Considered that low dose exposure to endocrine disruptor DDT irreversibly depresses expression of membrane glycoprotein sodium iodide symporter, which provides iodine uptake by the thyroid gland. After-birth exposure impairs compensatory activation of proliferation and increase in number of sodium iodide symporter-producing cells.